Issues and Patterns of Writing Issues Through Practical Journals Among Students at the Institute of Teacher Education, Tun Hussein Onn Campus, Batu Pahat - Kayar, Rosly; Mohd Kusrin, Zaiha; Mohd Sopah, Faridah; Borham, Abd. Shakor (Journal of Social Transformation and Regional Development, 2021)
This study aims to analyze issues, issue writing patterns, and reflective writing in the PISMP trainee teacher practicum journal, at Tun Hussein Onn Campus Teacher Education Institute, Batu Pahat. This study involved a total of 40 journal reflection writings selected at random in 2019 for various options. Qualitative study through document analysis is used to analyze the reflective writing of trainee teachers. In this study, the data were obtained from the writing notes of the reflection journal of the trainee teacher during the practicum. The results show that the writing of trainee teacher issues is more focused on the student domain (18 issues), followed by students (15 issues) and pedagogy (1 issue). Students were found not to touch the school domain at all and there was writing the title of the issue presented in the practicum journal not clear the domain of the issue (6 issues). The findings of the study also show that 36 out of 40 journal writing titles are clearly written. This shows that only a small number of journal writing titles cannot be written clearly. These findings indicate that trainee teachers are less focused on school factors such as environment, basic facilities, and racial diversity in writing self-reflection. The practice of reflection through journal writing is a very important aspect of teacher training in motivating trainee teachers intrinsically to achieve professional development in the field of trainee teacher duties.